Peran Moderasi Motivasi Hedonis pada Pengaruh Promosi Penjualan terhadap Niat Penggunaan Ulang Layanan Dompet Elektronik di Kalangan Milenial - Zahra, Nafisah; Sanaji, Sanaji (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to determine the role of moderation of hedonic motivation in sales promotion on repurchase intention to use e-wallets by millennials. This research uses an online survey method. The sampling technique used is judgmental sampling. The respondents are users of e-wallet branded OVO payments. The sample used was 215 respondents. Data is processed using Moderating Regression Analysis (MRA). This study indicates that sales promotions and hedonic motivation have a significant effect on repurchase intentions, but there is no significant relationship between sales promotions with hedonic motivation to strengthen the effect of sales promotions on repurchase intentions.